Le sous-titrage de film ou la prise en compte d’une dialectique contextuelle - Eve Vayssière (Corela)
Subtitle translation is subjected to a dialectics of contexts. Indeed, the translator must take both intra-filmic and extra-filmic contexts into account. The notion of intra-filmic context implies taking into account the cinematographic language (images, language, sound), whose elements generate whole phenomenological units which give the spectator access to the meaning of the film. The extra-filmic context, on the other hand, refers to what surrounds the film, such as history, trends and techniques in film, or the culture of the target audience. The specifically transient aspect of this kind of translation results from the dynamic relationship between subtitling and the extra-filmic context within which it lies.